Association of Microcyst Formation in Spirillum itersonii with the Spontaneous Induction of a Defective Bacteriophage - Clark-Walker, G. D. (1969)
Mitomycin C and ultraviolet light were found to induce the formation of microcysts in Spirillum itersonii. These forms, as well as spontaneously occurring microcysts in this species, were found to contain phage tail parts, rhapidosomes, and a granular substance not seen in normal cells. It is suggested that microcysts are formed as the result of the induction of a defective phage. The production of phage lysozyme within the cell could lead to the formation of spherical forms as the cells lose their structural mucopeptide layer. Complete virus particles were not seen, nor was any biological activity demonstrated when the induced cultures were tested against two other strains of S. itersonii. The other strains of this bacterium also formed microcysts and phage tail parts when induced with mitomycin. Attempts to isolate an organism lacking the defective phage have been unsuccessful.